2023
DOI: 10.1200/jco.22.00739
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib Study of Telisotuzumab Vedotin in Combination With Erlotinib in Patients With c-Met Protein–Expressing Non–Small-Cell Lung Cancer

Abstract: PURPOSE Overexpression of c-Met protein and epidermal growth factor receptor ( EGFR) mutations can co-occur in non–small-cell lung cancer (NSCLC), providing strong rationale for dual targeting. Telisotuzumab vedotin (Teliso-V), a first-in-class antibody-drug conjugate targeting c-Met, has shown a tolerable safety profile and antitumor activity as monotherapy. Herein, we report the results of a phase Ib study ( NCT02099058 ) evaluating Teliso-V plus erlotinib, an EGFR tyrosine kinase inhibitor (TKI), in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 37 publications
(76 reference statements)
1
26
0
Order By: Relevance
“…Therefore, numerous clinical studies have shown preliminary efficacy using this approach. In patients with EGFR-mutant NSCLC and MET amplification with disease progression on EGFR TKI treatment, subsequent treatment with an MET inhibitor and EGFR-TKI combination rendered clinical benefits in a series of phase I/II studies (Table 1) [71][72][73][94][95][96][97][98][99][100][101]. The TATTON trial [71] demonstrated the clinical benefits of osimertinib plus savolitinib in patients with previously treated EGFR-mutant MET-amplified NSCLC, with an objective response rate (ORR) of 44%.…”
Section: Drug Combination Strategies To Overcome Secondary Met Amplif...mentioning
confidence: 99%
“…Therefore, numerous clinical studies have shown preliminary efficacy using this approach. In patients with EGFR-mutant NSCLC and MET amplification with disease progression on EGFR TKI treatment, subsequent treatment with an MET inhibitor and EGFR-TKI combination rendered clinical benefits in a series of phase I/II studies (Table 1) [71][72][73][94][95][96][97][98][99][100][101]. The TATTON trial [71] demonstrated the clinical benefits of osimertinib plus savolitinib in patients with previously treated EGFR-mutant MET-amplified NSCLC, with an objective response rate (ORR) of 44%.…”
Section: Drug Combination Strategies To Overcome Secondary Met Amplif...mentioning
confidence: 99%
“…Conversely, ORR was 40% and DCR was 80% in EGFR WT patients (n 5 5). 65 The Luminosity trial was conducted to evaluate c-MET potential predictive biomarkers for Teliso-V treatment. In the nonsquamous EGFR WT subgroup, the ORR was 53.8% in c-MET high and 25% in c-MET intermediate (c-Met overexpression high: ≥50% tumor cells at 31 intensity; intermediate: 25%-49%).…”
Section: Metmentioning
confidence: 99%
“…In a phase Ib study, Teliso-V was evaluated in combination with erlotinib in patients with c-MET-positive NSCLC. 65 In the population of EGFR mutation (del19 or L858R)–positive patients at resistance to EGFR TKI (n = 28), ORR was 32.1% and DCR was 85.7%, with an mPFS of 5.9 months. In those EGFR mutation–positive patients with high c-MET expression (n = 15), ORR was 52.6%.…”
Section: Introductionmentioning
confidence: 98%
“…In the companion to this article, Camidge et al 7 described the safety and preliminary activity of telisotuzumab vedotin (Teliso-V), an antibody-drug conjugate (ADC) targeting MET, in combination with epidermal growth factor receptor (EGFR) kinase inhibitor erlotinib in patients with MET protein-expressing NSCLC. Teliso-V is the first-in-class therapeutic to target MET as a tumor-associated antigen in tumors with high MET expression and delivers monomethyl auristatin E (MMAE) as a cytotoxic payload to the cells (Fig 1).…”
mentioning
confidence: 99%
“…Camidge et al 7 explored the safety and efficacy of the combination of Teliso-V and the first-generation EGFR kinase inhibitor erlotinib in patients with high MET expression and oncogenic EGFR in patients with NSCLC after prior progression after EGFR inhibitor treatment. In total, 36 of 42 patients were efficacy evaluable with a median progression-free survival of this group of 5.9 months (95% CI, 2.8 to not reached).…”
mentioning
confidence: 99%